Professional Cloud Architect Google Cloud Certification Guide - Second Edition - Cłapa, Konrad; Gerrard, Brian; Liang, Yujun (Packt Publishing, 2021)
Become a Professional Cloud Architect by exploring the essential concepts, tools, and services in GCP and working through practice tests designed to help you take the exam confidently Key Features Plan and design a GCP cloud solution architecture Ensure the security and reliability of your cloud solutions and operations Assess your knowledge by taking mock tests with up-to-date exam questions Book Description Google Cloud Platform (GCP) is one of the industry leaders thanks to its array of services that can be leveraged by organizations to bring the best out of their infrastructure. This book is a comprehensive guide for learning methods to effectively utilize GCP services and help you become acquainted with the topics required to pass Google's Professional Cloud Architect certification exam. Following the Professional Cloud Architect's official exam syllabus, you'll first be introduced to the GCP. The book then covers the core services that GCP offers, such as computing and storage, and takes you through effective methods of scaling and automating your cloud infrastructure. As you progress through the chapters, you'll get to grips with containers and services and discover best practices related to the design and process. This revised second edition features new topics such as Cloud Run, Anthos, Data Fusion, Composer, and Data Catalog. By the end of this book, you'll have gained the knowledge required to take and pass the Google Cloud Certification - Professional Cloud Architect exam and become an expert in GCP services. What you will learn Understand the benefits of being a Google Certified Professional Cloud Architect Find out how to enroll for the Professional Cloud Architect exam Master the compute options in GCP Explore security and networking options in GCP Get to grips with managing and monitoring your workloads in GCP Understand storage, big data, and machine learning services Become familiar with exam scenarios and passing strategies Who this book is for If you are a cloud architect, cloud engineer, administrator, or any IT professional looking to learn how to implement Google Cloud services in your organization and become a GCP Certified Professional Cloud Architect, this book is for you. Basic knowledge of server infrastructure, including Linux and Windows Servers, is assumed. A solid understanding of network and storage will help you to make the most out of this book.